Solve the following pair of simultaneous equations 1)x+3y=11 2)3x+y=9

Rearrange equation 2 to make y the subject, then substitute the y expression into equation 1 and collect like terms: 3x+y=9 -->> y=9-3x x+3y=11 -->> x+3(9-3x)=11 -->> x+27-9x=11 -->> 27-11=8x -->> 16=8x -->> 16/8=x -->> x=2 Now that the x term is determined this value can be substituted into either equation 1, equation 2 or the rearranged equation 2 (the rearranged equations is ideal in this case since y is the subject and the then re-arrange is done all we need to do is substitute in the x term): y=9-3x -->> y=9-(3*2) -->> y=9-6 --> y=3 Answer: (2,3)

Answered by Tutor94832 D. Maths tutor

6855 Views

See similar Maths GCSE tutors

Related Maths GCSE answers

All answers ▸

Show that the lines A: y= 2x-5. and the line B: 2y-4x+3=0 are parallel.


Why can you not divide expressions by common factors?


Vectors a and b are defined by a = 2i + 3j and b = 4i - 2j, find 3a-b in terms of i and j


Find the solutions to the following equation x^2 - 5*x + 6 = 0


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences